Comparison of organoleptic quality of coffee (Coffea arabica L.) in Puno (Peru) and La Paz (Bolivia) - Ramos Cotacallapa, Edwen (2019)
57 samples of 500 g of coffee were evaluated to compare the quality of coffee cup, in the rural sectors of the San Juan del Oro areas in Sandia - Puno and Apollo in Franz Tamayo - La Paz. Both production areas are located in an ecological floor that varies between 1300 to 1400 msnm, this being an important factor, since high-quality coffee is obtained at more than 1200 msnm. For the evaluation of the samples in each production area of San Juan del Oro and Apollo, two samples (500g each) were made, first at 10% and second at 30% of the best samples for the evaluation of mixtures or blends. The best quality coffee was obtained 88.7 evaluation points of coffee beans from San Juan del Oro and 86.5 points in Apolo. The best cup organoleptic profile was presented in San Juan del Oro coffee with notes of "floral, honey, jasmine, complex", while in Apollo it was "citrus, floral, tangerine", resembling the qualities "floral, honey, and fruit flavor. " Based on the coffee classification of the Specialty Coffee Association of America, 55.4% of the coffee studied is in the special coffee category and 44.4% coffee of special origin. It is concluded that the best quality coffee is from San Juan del Oro; I do not enter Apolo, a production with better moisture conservation in parchment grain was observed, determining that there are organoleptic differences in both production areas and similar organoleptic profiles.